Ultrasonography reference values for the calcaneus in children and adolescents living at high altitude in Peru - Fuentes-López, Jose; Vidal-Espinoza, Rubén; Mamani-Luque, Ofelia; Ibanez-Quispe, Vladimiro; Villegas-Abrill, Claudia; Canqui-Flores, Bernabé; Mendoza-Mollocondo, Charles Ignacio; Sanchez-Macedo, Lucila; Cossio-Bolaños, Marco; Gomez-Campos, Rossana (Frontiers in Endocrinology, 2025)
ObjectiveThe evaluation of bone health during the growth stage is extremely important, as it is a key factor to prevent bone diseases in adulthood. The objectives of the study were: a) to verify if there are differences in bone health with other geographic regions, b) to develop bone health curves using quantitative ultrasonography (QUS) through the Broadband Ultrasonic Attenuation (BUA) parameter in children and adolescents residing in a high altitude region of Peru and c) to determine specific cut-off points for bone health assessment in this particular population.MethodsA cross-sectional study was carried out in schoolchildren in a high altitude region of Peru. The sample consisted of 1468 children and adolescents (724 males and 744 females). The age range was 6.0 to 17.9 years old. Weight and height were evaluated. Body Mass Index (BMI) was calculated. Bone quality was evaluated by quantitative ultrasonography (QUS) of the calcaneus. The parameters measured were Speed of Sound (SOS, m/s); Broadband Ultrasonic Attenuation (BUA, dB/MHz); and Bone Quality Index (BQI= αSOS+αBUA, αβ: temperature corrections).ResultsThere were small discrepancies in bone health (BUA) between studies from various geographic regions. Values differed across all age ranges from ~0.36 to ~10.86 in males and from ~0.26 to ~6.68 in females. At later ages during adolescence the values are relatively similar, reaching a plateau around 16 and 17 years of age. Percentiles were calculated for BUA by age and sex. Sensitivity and specificity values in females are slightly higher relative to males. However, the Youden Index reflects 0.84 for both sexes and the appropriate cut-off point for men is ≤67.8 and for women is ≤63.7.ConclusionThe study demonstrated that there are small discrepancies in bone health (BUA) among children between children and adolescents from different geographic regions. These findings support the creation of specific references and cut-off points for bone health in the pediatric population of a high altitude region of Peru. The results suggest the application of percentiles for the assessment of bone health in school and epidemiological contexts.